2008
DOI: 10.1080/15287390701838796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Contamination with Antibiotic Resistant and Enterotoxigenic Fecal Coliforms in Treated Drinking Water

Abstract: Pollution indicator bacteria such as coliforms, fecal coliforms, and fecal streptococci were enumerated using a multiple-tube fermentation method in 100 treated drinking-water samples from 20 locations in residential, commercial, and industrial areas of a tropical city during summer. Thirty-four percent of the samples were bacteriologically nonpotable. Maximum coliform-contaminated (27%) samples were derived from industrial areas, while samples contaminated with fecal coliform (23%) and fecal streptococci (20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
22
2
1
Order By: Relevance
“…However, Toroglu et al (2005) has been reported that 40% of the coliforms isolated from a river in southern Turkey showed multiple antibiotic resistance (MAR). On the other hand, Pathak and Gopak (2008) have reported that coliforms identified as E. coli, Klebsiella sp., Enterobacter sp., and Citrobacter sp. were present in treated drinking water samples.…”
Section: Discussionmentioning
confidence: 97%
“…However, Toroglu et al (2005) has been reported that 40% of the coliforms isolated from a river in southern Turkey showed multiple antibiotic resistance (MAR). On the other hand, Pathak and Gopak (2008) have reported that coliforms identified as E. coli, Klebsiella sp., Enterobacter sp., and Citrobacter sp. were present in treated drinking water samples.…”
Section: Discussionmentioning
confidence: 97%
“…A number of previous studies have reported that ARB are common in drinking water (2,3,19,25,33). We added to these studies by testing water both before and after treatment, as well as tap water.…”
mentioning
confidence: 99%
“…The present study also revealed that 23% piped supply and 20% groundwater samples from hand pumps as well as tube wells has been found to be bacteriologically contaminated in the Lucknow City (Table 2). Our earlier studies also showed prevalence of bacterial Values are as micrograms per litre based on triplicate analysis; RSD is less than 9% ND not detected a Five samples were analyzed from each location contamination in chlorinated piped water supplies (Pathak and Gopal 2008). For bacterial contamination of water, broken pipes and loose joints in the distribution system are also responsible for seepage and back suction.…”
Section: Resultsmentioning
confidence: 98%
“…Earlier studies performed in this area were mainly for parameters of bacteriological quality (Pathak and Gopal 2008;Grover and Thakur 2001;Ramteke et al 1992), physicochemical (Jameel 2002), heavy metals (Dixit et al 2003) and pesticide residue analysis (Sankararamakrishnana et al 2005). However, adequate information is not available on the status of urban drinking water quality in the tropics with respect to contamination with bacteria, pesticides and heavy metals.…”
Section: Introductionmentioning
confidence: 99%